Molecular analysis of mucopolysaccharidosis type IIIB in Portugal: evidence of a single origin for a common mutation (R234C) in the Iberian Peninsula - Mangas, Mariana (2012)
Mucopolysaccharidosis type IIIB (Sanfilippo B disease) is a rare autosomal recessive disorder caused by defective alpha-N-acetylglucosaminidase (NAGLU). We examined the NAGLU gene in 11 MPS IIIB Portuguese patients, having identified five novel (M1K, W147X, G304V, S522P, and R533X) and four previously reported mutations (W168X, R234C, R565W and R643C). R234C attained the high prevalence of 32% of the mutated alleles. Because R234C had already been reported to be common in Spanish patients, a haplotypic analysis was conducted to address the question of its origin in the Iberian Peninsula. Three neutral markers were studied that allowed for the identification of the probable founder haplotype (174-234-G) on which R234C arose. The sharing of the ancestral haplotype by Portuguese and Spanish patients clearly implied a common origin of the mutation in Iberia, through an event that was inferred to have been rather recent. Therefore, the reconstructed history of R234C explains the high incidence of the mutation in Iberian patients with Sanfilippo B disease.